EVALUASI PERAN GURU DALAM PENERAPAN KURIKULUM MERDEKA PADA PEMBELAJARAN MATEMATIKA - Nelis Syayidah; Yeva Kurniawati (Universitas Muhammadiyah Semarang, 2024)
The role of teachers is as teachers, mentors, and educators. As a teacher, teachers carry out education, creating effective and enjoyable learning. As mentors, teachers help students recognize themselves and their problems and solve their problems. As educators, teachers facilitate the process of recognizing and maturing students through learning. This research aims to find out evaluation of the role of teachers on the implementation of an independent curriculum mathematics learning. The type of research used is descriptive qualitative. This study examined mathematics teachers. The data collection method used was by conducting document analysis, observation, and interviews. The documents analyzed were teaching modules. Data analysis was conducted this was is done by minimizing amount of data, presenting data, and making conclusions. All of this was done using the triangulation techniqueThe results of observation and interview results are analyzed using completeness and content of the documents.